Market versus state in building the aviation value chain - Günter Knieps (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2013)
The aim of this paper is to analyze the liberalization of the aviation value chain and the remaining role of government policy. In particular, the role of sector-specific regulation of monopolistic bottleneck components of the air traffic value chain is analyzed. For competition on air transport markets and groundhandling services to operate efficiently, non-discriminatory access to complementary monopolistic airport infrastructures must be guaranteed. In particular, the evolution of market driven slot allocation and the role of airport regulation is analyzed. Finally, the issue of airport subsidies is taken into consideration.
Keywords: 330